2021
DOI: 10.1021/acsanm.1c00603
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticle-Containing Colorimetric Contact Lenses for Noninvasively Monitoring Human Tear Glucose

Abstract: Noninvasive methods for monitoring diabetes are being developed to eliminate the need for invasive finger-prick testing. Here, we propose the noninvasive detection of tear glucose using contact lenses that contain cerium oxide nanoparticles (CNPs). We chemically conjugated CNPs with glucose oxidase (GOx) using poly(ethylene glycol) (PEG) (CNP-PEG-GOx). GOx oxidizes glucose into hydrogen peroxide, which rapidly (∼1 min) reduces colorless Ce 3+ to yellow Ce 4+ with high sensitivity (>0.1 mM). Then, the yellow CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…[35] Functional nanoparticles with unique properties, such as no/low cytotoxicity, excellent physical/chemical features, and drug-delivery ability, have also been employed to improve/integrate some SCL properties. [51,62,[88][89][90] For example, it has been reported that the nanoparticles were incorporated into CL polymers and gelling systems to enhance mechanical strength and elasticity of CLs. [34] For example, organic dyeencapsulated silica nanoparticles were applied with PHEMA or PDMS to obtain precise biosensing capability, with the detection sensitivity of 0.5-5 mM of blood glucose.…”
Section: Encapsulationmentioning
confidence: 99%
“…[35] Functional nanoparticles with unique properties, such as no/low cytotoxicity, excellent physical/chemical features, and drug-delivery ability, have also been employed to improve/integrate some SCL properties. [51,62,[88][89][90] For example, it has been reported that the nanoparticles were incorporated into CL polymers and gelling systems to enhance mechanical strength and elasticity of CLs. [34] For example, organic dyeencapsulated silica nanoparticles were applied with PHEMA or PDMS to obtain precise biosensing capability, with the detection sensitivity of 0.5-5 mM of blood glucose.…”
Section: Encapsulationmentioning
confidence: 99%
“…110 Copyright 2021, Elsevier B.V. (D) CNP-PEG-GOx-laden contact lenses for colorimetric monitoring tear glucose. 111 Copyright 2021, American Chemical Society. (E) A remotely controllable smart contact lens for diabetic diagnosis and therapy.…”
Section: Tearmentioning
confidence: 99%
“…(C) Plasmonic contact lens composed of SERS-LM for the selective glucose detection in human tears 110. Copyright 2021, Elsevier B.V. (D) CNP-PEG-GOx-laden contact lenses for colorimetric monitoring tear glucose 111. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%
“…Recently, Park et al . developed a biocompatible biosensor of a nanoparticle-embedded contact lens (NECL) composed of complexes of cerium oxide nanoparticles (CNPs), glucose oxidase (GOx), and a polyethylene glycol (PEG) 20 . After reacting with tear glucose and H 2 O 2 , NECLs are oxidized and changed into a yellowish color.…”
Section: The Current Colorimetric Analytical Devices With Nanozymesmentioning
confidence: 99%
“…Nanozyme-based biosensors mainly detect color in a qualitative manner 19 , 20 . Therefore, for quantitative measurement of glucose concentration, many algorithms have been developed in different color spaces (RGB, CMYK, HSB/HSL, CIE XYZ, L*a*b*, and YUV models) to analyze color variations.…”
Section: Introductionmentioning
confidence: 99%